KAJIAN KRITIS TERHADAP PEMIKIRAN TENTANG JIWA (AL-NAFS) DALAM FILSAFAT ISLAM - ., Asmullah; Iqbal, Muhammad (Inspiratif Pendidikan, 2022)
The main problem in this paper is trying to examine or elaborate in depth about the nature and thoughts of Islamic philosophers on the soul (nafs). To answer this problem, the author tries to trace or trace some of the opinions of experts regarding the soul (nafs) in various books or related writings in order to obtain a more in-depth and accurate understanding. The results of the study of this paper show that the essence of the soul (nafs) comes from the substance of God which has its own form and is different from the body (jism). But cannot be separated. He is like the sun with its light. The soul created by God is different from the body and both have their own form. However, between body and soul both must be considered because they both need food. The soul needs spiritual nourishment, thinking, learning, and so on. While the body (jism) requires food, drink, exercise, sex, rest and so on. The soul (nafs) is something that is very essential and has an effect on humans. Therefore, the soul (nafs) must be trained in such a way so that it can become good, healthy, live and even become holy.